Urgensi Media Sosial Dan Keterampilan Kewirausahaan Menuju Keberhasilan - Fauzan Azhima Sirait; Nur Dahyanti; Sylvi Marsella Diastami; Suwandi Suwandi (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to be able to able to describe and find out about the urgency of social media and entrepreneurial skills towards success. Social media is very influential on entrepreneurial success, especially in the increasingly developing and advance digital era. Entrepreneurs themselves have the meaning of people who change the value of resources, labor, materials and other production factors to be greater than before and also people who make changes, innovate and use new methods. Skills are also really needed in carrying out entrepreneurial activities, because if an entrepreneurial does not have skills that are able to develop rapidly. Therefore, social media and skills have a big influence in entrepreneurship.